Nilai Kejujuran Pada Film Penyalin Cahaya: Kajian Sosiologi Sastra - Yashinta Nur Zakiyyah; Eko Cahyo Prawoto (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
Language is the medium used for writing literary works, while literature is a social institution that illustrates language in social life. Based on its type, literary works are divided into 3, namely poetry, prose and drama. Film is included in the type of drama literary works that are conveyed visually. In the film there are building elements that make the film meaningful and contain a moral message. The moral message in film is very important, because moral values ​​can be used as an understanding in society. A very important moral value is honesty. In this research, the researcher discusses the literary work of a film entitled Copying Light. The purpose of this research is to find out and describe the forms of moral honesty values ​​contained in the film Copying Light. The approach used in this research is qualitative research. The data collection technique in this study was to download the Netflix application, create a Netflix account, search for Light Copy films, watch films and make transcripts of the data results. The data obtained were then analyzed using data presentation and data verification techniques. To test the validity of the data, the researcher used theoretical triangulation, namely comparing the theory carried out with a number of theories so that it could deceive some data. The results of the study show that honest moral values ​​are moral attitudes that are forthright, able to be oneself, and honest according to the facts.